The Internalization of the Value of Mutual Cooperation in Strengthening National Identity - Nugraha, Nugraha; Syaifullah, Syaifullah; Supriyono, Supriyono (De Cive : Jurnal Penelitian Pendidikan Pancasila dan Kewarganegaraan, 2025)
Gotong royong is an activity that is characteristic of Indonesian society that has been carried out since the past until now. However, at the time in Indonesian society has begun to experience changes towards the fading of gotong royong activities due to the influence of the globalization era. The purpose of this study is to strengthen the values of gotong royong as a strengthening of national identity in the era of globalization. This study uses a case study by relying on sources that have good credibility. The novelty of this study lies in its focus on gotong royong not merely as a traditional cultural value, but as a strategic cultural mechanism for resisting the erosion of national identity in the face of global cultural homogenization. Unlike earlier works that treat gotong royong as a static heritage, this research repositions it as a dynamic sociocultural resource that can be adapted and reintegrated into modern institutions such as schools, urban communities, and digital civic spaces.  Based on the results of the study, it can be concluded that real efforts are needed from all parties, both families, schools, communities and governments in an effort to internalize the values of ggotong royong  in order to strengthen the identity of the Indonesian nation.